Vali pour une reine morte de Boris Gamaleya, épopée lyrique de la Réunion - Annie Urbanik-Rizk (Carnets)
The creole activist Boris Gamaleya is a poet who sings his lost island in his first poetry work Vali for a dead queen. Forced into exile in mainland France because of political ostracism, he doesn’t just exude nostalgia for this southern land, he also evokes with fury the tragic destiny of this former colony. The vali, a malagasy musical instrument, made out of strings and bamboo was introduced into the Mascareignes by slaves. It suggests the epical dimension of this long poem. It symbolizes the liberty that the escaped slaves, who have found refuge in the most inaccessible peaks, have tried to find. The dead queen is no other than Rahariane, the queen of the escaped slaves who embodies the sensuality of a feminized island, deadly wounded and then, transfigured by the power of words.